code-mixing on Facebook postings by EFL students: A small scale study at an SMP in Tangerang - Bayu Kurniawan (Universitas Katolik Indonesia Atma Jaya, 2016)
This study aims to analyze the use of English, in terms of code mixing forms, and its motivations by EFL teenager learners. The participants of this study are three students in the age range of 12-14 year’s old (grade 8th and 9th) in a junior high school in Tangerang, Indonesia. The data was a one week Facebook postings from the students Facebook page. Content analysis was used as a method for data analysis. In addition, interview was also conducted to find out the participants’ motivation in using English on their Facebook posts. The research findings showed that English is frequently used by students in social media to perform code-mixing which are present in caption, status, hashtag, and comments. Using Hoffman’s categorization (1991), reasons for code-mixing are identified as follows: 1) talking about a particular topic, 2) quoting somebody else’s statements, 3) being emphatic about something, 4) interjection (inserting sentence fillers or sentence connectors), 5) indicating pride and 6) limited words.